Erasing the invisible hand : essays on an elusive and misused concept in economics - Samuels, Warren J., 1933-; Johnson, Marianne F. (Marianne Frances); Perry, William H. (Cambridge : Cambridge University Press, 2011)
This book examines the use, principally in economics, of the concept of the invisible hand, centering on Adam Smith. It interprets the concept as ideology, knowledge, and a linguistic phenomenon. It shows how the principal Chicago School interpretation misperceives and distorts what Smith believed on the economic role of government. The essays further show how Smith was silent as to his intended meaning, using the term to set minds at rest; how the claim that the invisible hand is the foundational concept of economics is repudiated by numerous leading economic theorists; that several dozen identities given the invisible hand renders the term ambiguous and inconclusive; that no such thing as an invisible hand exists; and that calling something an invisible hand adds nothing to knowledge. Finally, the essays show that the leading doctrines purporting to claim an invisible hand for the case for capitalism cannot invoke the term but that other nonnormative invisible hand processes are still useful tools.
Adam Smith's invisible hand and the Nobel prize in economic sciences -- The political economy of Adam Smith -- On the identities and functions attributed to the invisible hand -- Adam Smith's history of astronomy argument : how broadly does it apply? And where do propositions that 'sooth the imagination' come from? -- The invisible hand, decision making, and working things out: conceptual and substantive problems -- The invisible hand in an uncertain world with an uncertain language -- The invisible hand as knowledge -- The invisible hand and the economic role of government -- The survival requirement of Pareto optimality -- Conclusions and further insights.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Smith, Adam, -- 1723-1790.; Free enterprise; Economics; Capitalism